Stratigraphy and vegetation signals from an upland, landslide-dammed, paleolake during the Last Glacial-Interglacial Transition, Waipaoa Sedimentary System, Hikurangi Margin, eastern North Island, New Zealand. Issue 1 (2nd January 2022) - Marden, Michael; Holt, Katherine; Ryan, Matthew; Carrasco, Joe; Marsaglia, Kathleen; Kirby, Matthew; Palmer, Alan
ABSTRACT: A recently discovered upland paleolake (Redpath Lake) provides evidence of the expansion of lowland podocarp temperate forest to higher elevations within the tectonically active Waipaoa Sedimentary System (WSS), eastern North Island, New Zealand, during the Last Glacial-Holocene Transition. Interpreted as a localised landslide-dammed lake, lithofacies analyses indicate deposition and preservation in a low energy, sub-aqueous, lacustrine environment. Robust Bayesian-derived age-depth models constrained by key tephra fall beds and independent 14 C dating ( n = 7) indicate storm-bed frequency of c. 226 yrs on average. The absence of extensive soft-sediment deformation or lake-bed tilting implies that seismic shaking was insignificant during the Lake's c. 12 ka yr (17.3–5.5 cal ka BP) existence. Pollen spectra extracted from lacustrine deposits include a mix of montane shrubland and lowland podocarp species spanning a well-dated c. 2200-year (c. 16.3–14.1 cal ka BP) period coeval with a phase of significant climate amelioration (late NZCe–5/NZce-4 mild episode), based on biotic proxies during the latter part of the climatically variable Last Glacial-Interglacial Transition (LGIT) (c. 18.2–11.8 cal ka BP). These pollen spectra represent the first New Zealand record of replacement of montane shrublands in terrestrial uplands of the WSS were replaced by lowland podocarp forest.